DETERMINATION OF AGROINDUSTRY DEVELOPMENT STRATEGY FOR SMALL AND MEDIUM ENTERPRISE CLUSTERS OF REGIONAL EXCELLENCE BASED ON LOCAL AGRICULTURAL RESOURCES TO SUPPORT THE ECONOMY IN WONOGIRI REGENCY - Wardani, Irma; Dewi, Tria Rosana; Nugroho, Wahyu Tulus (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
In supporting the government's progress and future development, it is necessary to make the agricultural sector-based industry Small and Medium Enterprises the leading sector in the development of a region. Wonogiri Regency is one of the regencies in Central Java that has enough potential to develop Small and Medium Enterprise agroindustry. The objectives of this study are 1) to determine the internal and external factor environment in the Agroindustry Small and Medium Enterprise Leading Cluster and 2) to select alternative strategies for business actors using the methods used in the IFE and EFE Matrices, SWOT Analysis, and QSPM. The results of the study are 1) the strategies used are market penetration strategies, market development, and product development, and 2) the selected strategy is market development. Strategies that can be used in market development in cashew clusters are 1) utilization of information technology, 2) expanding the network/marketplace, 3) revitalization of cashew crops, and 3) training of human resources to increase productivity. Keywords: Development, Agroindustry, Cashew Cluster, SWOT, QSPM